OSCE in pediatrics - Jain, Vivek (Jaypee Brothers Medical Publishers, 2016)
He new edition includes many new cases and covers numerous topics including genetics, neurology, drugs and vaccines, neonatology, cardiovascular system, endocrinology and much more. Enhanced by nearly 240 clinical photographs and illustrations, the book also includes multiple choice questions to help students prepare for MRCPCH and US Specialty Board examinations